On the development of i-Community to improve production of off-season longan - Ramingwong,S. (INSInet Publications, 2015)
Longan is one of the most important Thai economic fruits, accounting for more than 120 million USD of market value yearly. Alternative to typical seasonal longan, off-season production can increase marketing potential to the agro-industry where price is more attractive. However, problems exist within the industry where information sharing is limited within and between supply chain members. Therefore, it is the aim of the study to develop i-Community where news, knowledge and information can be easily accessible. Highlighted information includes the forecasted production output in terms of harvesting period, quality and quantity of the crop by the developed fuzzy neural network engine.